Secondary teachers’ competencies and attitude: A mediated multigroup model based on usefulness and enjoyment to examine the differences between key dimensions of STEM teaching practice - Fabiola Sanda Chiriacescu; Bogdan Chiriacescu; Alina Elena Grecu; Cristina Miron; Ion Ovidiu Panisoara; Iuliana Mihaela Lazar (PLoS ONE, 2023)
This research explores the mediating role of perceived usefulness and enjoyment of science, technology, engineering, and mathematics (STEM) teaching practice between secondary teachers’ competencies and attitudes in the formal educational context. Also, the research aimed to examine if the relationships between model constructs differ by STEM teaching practice dimension (e.g., Inquiry-based learning (IBL) and Integration of STEM content (INT)). We synthesized the will, skill, tool model (WST), technology acceptance model (TAM) and flow theory (FLT) to develop a theoretical model predicting teacher attitude under the influence of Competencies, Perceived Usefulness and Perceived Enjoyment. Therefore, a mediated multigroup model with validated data from three hundred Romanian secondary teachers who completed questionnaires related to their competencies, perceived usefulness, enjoyment, and attitude toward STEM teaching practices was used. Two comparative teacher survey studies were carried out: one for IBL and one for INT. There are direct and positive relationships between Competencies and Attitude, Competencies and Enjoyment, Competencies and Usefulness, and Enjoyment and Attitude for both IBL and INT teaching practices. The partial least squares path modeling (PLS-SEM) results showed that the control variables had no significant impact on attitude. This research supports evidence for the belief that teachers’ competency is a key predictor of attitude. Precisely, the positive strong direct effect of Competencies on Attitude is similar for IBL (β = 0.49, t = 7.46, p < 0.001; f2 (Effect size) = 0.29) with for INT teaching practice (β = 0.46, t = 6.46, p < 0.001; f2 (Effect size) = 0.22). Interestingly, this research showed that the perceived Usefulness and Enjoyment partially mediated the association between Competencies and Attitude in both case studies. Understanding the mediating role of perceived usefulness and enjoyment for each STEM practice would help teachers successfully implement STEM education.